Analisis Variabel yang Memengaruhi Konsumsi Energi Terbarukan di Indonesia Menggunakan Error Correction Model - Arrohmah, Laila; Sukim, Sukim (Politeknik Statistika STIS, 2024)
Energy has an important role to support life. Energy consumption that focuses on non-renewable natural resources or what is usually called fossil energy can have negative effects on the environment. For this reason, alternative efforts are needed to provide energy that can replace it, namely renewable energy. The aim of this research is to analyze variables that are thought to influence renewable energy consumption in Indonesia in 2003-2021. The analysis is carried out descriptively and inferentially. Descriptive analysis displays a line chart to provide an overview of developments in the volume of renewable energy consumption in Indonesia. Inferential analysis was carried out in a time series using the Error Correction Model (ECM). The results of the analysis show that in the long term the variables economic growth, population, fossil energy consumption, and average years of schooling have an influence on renewable energy consumption in Indonesia on 2003 2021. In the short term, the variables economic growth, fossil energy consumption, and average years of schooling influence renewable energy consumption in Indonesia on 2003- 2021.